A prospective study of endometriosis and its outcome at tertiary care centre - Ninama, Shilpa; Rami, Bijal D. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: This study was conducted to detect various presenting clinical features, type and severity of pelvic endometriosis according to revised American fertility society classification. Objective of this study was to assess outcome of endometriosis after medical and surgical treatment in form of pregnancy, reduction of symptoms like dysmenorrhoea, dyspareunia and others. Methods: This prospective study conducted at one of tertiary care teaching institutes for period of 3 years from January 2011 to December 2013. A total number of 100 patients of pelvic endometriosis were examined and divided according to Revised American Fertility Society Classification on bases of severity, type and clinical features and laparoscopic findings. After 1 year of follow up, outcome assessed after completion of medical and surgical treatment in form of pregnancy, reduction of dysmenorrhoea and dyspareunia and other symptoms. Results: This study showed most affected patients (46%) belongs to 26-30 years of age group, dysmenorrhoea was the most common presenting symptoms in 76% patients. Most common site affected (52%) was ovaries. Laparoscopy was done in 86% patients. Most patients (44%) were benefited with fulguration of endometriotic nodules. 62% of patients were given oral contraceptive pills or progesterone pills after definitive surgery as freely available in Governmental setup and fewer side effects as compared to Danazol and GnRH analogues. 40 patients became pregnant after medical and surgical treatment, where 60 patients had reduced dysmenorrhoea and 20 patients had reduced dyspareunia. Conclusions: Laparoscopy is gold standard diagnostic as well as therapeutic tool in pelvic endometriosis as it can rule out other causes of infertility without interfering normal anatomy.